2020
DOI: 10.21037/atm-20-5454
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin-3 polymorphisms and pulmonary fungal disease in non-neutropenic patients

Abstract: Background: Pentraxin 3 (PTX3) plays a non-redundant role in innate immunity against fungal diseases. Although single nucleotide polymorphisms (SNPs) of PTX3 are associated with a higher risk of invasive aspergillosis among the immunosuppressed population and chronic obstructive pulmonary disease patients, it is unknown whether PTX3 genetic variants influence the risk of pulmonary fungal disease in immunocompetent patients.Methods: To investigate the association between PTX3 gene polymorphisms and pulmonary my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Moreover, they further elucidated that PTX3 deficiency in h2/h2 type affects the antifungal capacity of neutrophils, presumably due to messenger RNA instability, and this can be corrected after supplementing of exogenous PTX3. Tiantian Tang et al conducted a case–control study to show that PTX3 rs2305619 had no genotypic distribution differences, but rs3816527 was associated with invasive pulmonary aspergillosis (IPA) in non-neutropenic patients [ 24 ]. However, it is difficult to directly compare our data, and several points should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they further elucidated that PTX3 deficiency in h2/h2 type affects the antifungal capacity of neutrophils, presumably due to messenger RNA instability, and this can be corrected after supplementing of exogenous PTX3. Tiantian Tang et al conducted a case–control study to show that PTX3 rs2305619 had no genotypic distribution differences, but rs3816527 was associated with invasive pulmonary aspergillosis (IPA) in non-neutropenic patients [ 24 ]. However, it is difficult to directly compare our data, and several points should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Fisher et al reported that PTX3 genetic variants rs7252229 and rs3816527 may be associated with invasive aspergillosis following hematopoietic cell transplantation [34]. PTX3 SNP rs3816527 has been reported to be associated with invasive pulmonary aspergillosis in non-neutropenic patients [35]. Zhang et al suggested that PTX3 genetic variant rs3845978 was related to ankylosing spondylitis, but rs2305619 was not [36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they further elucidated that PTX3 de ciency in h2/h2 type affects the antifungal capacity of neutrophils, presumably due to messenger RNA instability, and this can be corrected after supplementing of exogenous PTX3. Tiantian Tang et al conducted a casecontrol study to show that PTX3 rs2305619 had no genotypic distribution differences, but rs3816527 was associated with IPA in non-neutropenic patients 23 . However, it is di cult to directly compare our data, and several points should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%